Guidelines for Cultivating Innovators to Foster Sustainable Innovation under the PPC INNOVATE Framework of Phitsanulok Polytechnic College - นอหน่อ สมศักดิ์; บุญโสภา พินิจ; สุ่มมาตย์ วราภรณ์; แย้มชุติ นภวรรณ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to propose guidelines for cultivating innovators to achieve sustainable innovation under the PPC INNOVATE model and to examine the satisfaction and outcomes resulting from the implementation of these guidelines at Phitsanulok Polytechnic College. The population for this study consisted of 72 participants, including administrators, teachers, and educational personnel of Phitsanulok Polytechnic College. The purposive expert group comprised five specialists in educational administration, innovation and inventions, curriculum development, research and evaluation, and industry sector representatives. Basic statistical methods, including percentage, mean, and standard deviation, were employed for data analysis. The research findings revealed that the guidelines for cultivating innovators to achieve sustainable innovation under the PPC INNOVATE model at Phitsanulok Polytechnic College were implemented with an emphasis on participation, collaboration, and creativity in educational institution management. Overall satisfaction with the guidelines was at the highest level, with a mean score of 4.63. When considering each aspect, the highest mean score was found in the outcomes dimension (mean = 4.70), followed by the effectiveness of the management model (mean = 4.66), both at the highest level. Furthermore, the outcomes of the guidelines were categorized into two types: 1) innovative inventions developed by the new generation, and 2) participation in the Honda Fuel Efficiency Competition.